Methodological considerations of electron spin resonance spin trapping techniques for measuring reactive oxygen species generated from metal oxide nanomaterials - Jeong, Min Sook (Sci Rep, 2016)
Qualitative and quantitative analyses of reactive oxygen species (ROS) generated on the surfaces of nanomaterials are important for understanding their toxicity and toxic mechanisms, which are in turn beneficial for manufacturing more biocompatible nanomaterials in many industrial fields. Electron spin resonance (ESR) is a useful tool for detecting ROS formation. However, using this technique without first considering the physicochemical properties of nanomaterials and proper conditions of the spin trapping agent (such as incubation time) may lead to misinterpretation of the resulting data. In this report, we suggest methodological considerations for ESR as pertains to magnetism, sample preparation and proper incubation time with spin trapping agents. Based on our results, each spin trapping agent should be given the proper incubation time. For nanomaterials having magnetic properties, it is useful to remove these nanomaterials via centrifugation after reacting with spin trapping agents. Sonication for the purpose of sample dispersion and sample light exposure should be controlled during ESR in order to enhance the obtained ROS signal. This report will allow researchers to better design ESR spin trapping applications involving nanomaterials.